Gender differences in cognitive benefits of meeting physical activity guidelines in older Chinese adults - Wang Li; Peiyou Chen; Aiyun Jiang; Fan Zhang; Zhijian Wu (Frontiers in Public Health)
ObjectiveThis study investigates the relationship between adherence to WHO physical activity guidelines and cognitive function in older Chinese adults, with a particular focus on gender-specific effects. We hypothesize that meeting physical activity guidelines is positively associated with cognitive function and that the magnitude of this association differs between men and women.MethodsWe conducted a cross-sectional study involving 308 community-dwelling older adults in Nanjing, China (mean age = 68.4 years, SD = 5.6). Participants were stratified by gender and age group (60–70 vs. 71–80 years). Physical activity was objectively measured using ActiGraph GT3X+ accelerometers, and cognitive function was assessed via the Montreal Cognitive Assessment (MoCA). Multivariable linear regression was used to examine associations between physical activity adherence and cognitive function, adjusting for age, education, BMI, and self-rated health. Gender differences were analyzed using ANOVA, and interaction terms were included to assess moderation effects.ResultsOlder adults meeting the WHO-recommended 150 min of moderate-to-vigorous physical activity per week had significantly higher MoCA scores than non-adherent individuals (β = 3.67, 95% CI: 3.04–4.29, p < 0.001; Cohen’s d = 0.85). Women showed greater improvements in executive function (β = 0.79, p = 0.043) and visuospatial abilities (β = 0.47, p = 0.017), while men demonstrated greater memory gains (β = 1.31, p < 0.001). A significant interaction between gender and physical activity adherence (p = 0.008) suggested distinct cognitive benefits across sexes.ConclusionAdherence to physical activity guidelines is associated with cognitive health in older adults, with gender-specific variations in cognitive benefits. These findings underscore the importance of tailored public health interventions that consider gender differences in cognitive aging to optimize cognitive outcomes.